1986
DOI: 10.1111/j.1476-5381.1986.tb14592.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized and intravenously administered leukotrienes: effects on the bronchoconstrictor potency of histamine in the guinea‐pig

Abstract: 1 The effects of leukotrienes C4 and D4 (LTC4 and LTD4), administered intravenously or by aerosol, on the bronchoconstrictor potency of intravenously administered histamine have been investigated in anaesthetized, mechanically ventilated guinea-pigs.2 LTC4 (2 nM) had no effect on either the ECv or the maximum contractile response to histamine on the isolated trachea of the guinea-pig. At 10 nM, LTC4 induced a rightward shift in the histamine concentration-response curve without affecting the maximum response.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…or LTC4 or LTD, (aerosol) enhanced airways responsiveness to histamine (i.v.) [14,15]. The time course of the enhanced airways responsiveness induced by exogenous LT aerosol was of comparable duration to that observed in the present study subsiding over a 40-60 min period.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…or LTC4 or LTD, (aerosol) enhanced airways responsiveness to histamine (i.v.) [14,15]. The time course of the enhanced airways responsiveness induced by exogenous LT aerosol was of comparable duration to that observed in the present study subsiding over a 40-60 min period.…”
supporting
confidence: 78%
“…LTs per se are implicated as mediators of increased airways responsiveness. LTB4 causes air-ways hyperresponsiveness in the guinea-pig [12] and studies from our laboratory have demonstrated that th e cysteinyl-containing leukotrienes, LTC, and LTD4, cause increased airways responsiveness to histamine in the guinea-pig in vivo by augmenting a cholinergic vagal afferent reflex mechanism [13][14][15]. The objective of the present study was to determine whether the release of arachidonic acid metabolites, particularly the LTs, mediate an altered airways sensitivity to histamine after acute exposure of guinea-pigs to Paf in vivo.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, following allergen challenge of sensitized subjects, the airways become hyperresponsive to histamine, methacholine, cold air and exercise, a state which may last for many weeks after a single allergen exposure [4]. The mechanisms iiwolved in the disordered airway physiology associated with hyperresponsiveness are diverse and involve the participation of inflammatory leucocytes with release of potent pro-inflammatory chemical mediators [1, [5][6][7]. In particular, eosinophilia is a marked feature of the human airways response to antigen challenge [8,9).…”
mentioning
confidence: 99%
“…Exogenous LTD4 increased airways responsiveness to histamine in the guinea-pig (Stewart et al, 1984;Fennessy et al, 1986) whereas in healthy humans LTD4 augmented airways responses to methacholine (Kern et al, 1986) and prostaglandin F2. (Barnes et al, 1984a) but not to histamine (Barnes et al, 1984b).…”
Section: Discussionmentioning
confidence: 99%